The Public Library and Social Media. A Case Study from Tromsø, Norway - Skare, Roswitha (The University of Akron Press, 2018)
Source at https://ideaexchange.uakron.edu/docam/ . Introduction : Historically, archives, libraries and museums (ALM) have been perceived as institutions providing infrastructure for an open and enlightened public discourse. The Norwegian Public Libraries Act (Lov om folkebibliotek), for instance, focuses on public libraries being providers of knowledge and cultural expressions, agents of popular enlightenment, local meeting places and arenas of debate and participation in the public sphere.